2020
DOI: 10.1111/jan.14453
|View full text |Cite
|
Sign up to set email alerts
|

Improving mental health of student and novice nurses to prevent dropout: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 76 publications
(211 reference statements)
0
28
0
1
Order By: Relevance
“…In total, records 5,931 were retrieved. Additionally, three studies were identified from the reference lists of previously published literature reviews (Chesak et al, 2019 ; Ghawadra et al, 2019 ; Bakker et al, 2020 ). 5,892 records were left for screening after removing duplicates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, records 5,931 were retrieved. Additionally, three studies were identified from the reference lists of previously published literature reviews (Chesak et al, 2019 ; Ghawadra et al, 2019 ; Bakker et al, 2020 ). 5,892 records were left for screening after removing duplicates.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this fact rendered the comparison of the results difficult and based on this one might question their generalizability to other settings. Although previous research on stress reduction in health care providers has also identified the same methodological problem (e.g., Edwards and Burnard, 2003;Bakker et al, 2020), it still concerns. Furthermore, future research may pay more attention into different nursing specialties by developing strategies to meet the demands of non-hospital-based institutions (Bakker et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of academic life on the mental health of university students has already been widely reported (Pasic et al ., 2020). Poor mental health has been associated with a significant deterioration in academic performance (Hysenbegasi et al ., 2005) and also with students abandoning certain studies (Bakker et al ., 2020; Bowman et al ., 2020). This phenomenon is particularly relevant in degrees associated with health, such as nursing and medicine (Hughes & Byrom, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is particularly relevant in degrees associated with health, such as nursing and medicine (Hughes & Byrom, 2019). In fact, higher levels of depression and anxiety have been reported in students studying these subjects than other academic disciplines (Bakker et al ., 2020; Iorga et al ., 2018; Mitchell, 2018; Tung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%